Efficacy and Safety of 0.1% Cyclosporine a Cationic Emulsion in the Treatment of Severe Dry Eye Disease: A Multicenter Randomized Trial. Issue 4 (July 2016) - Leonardi, Andrea; Van Setten, Gysbert; Amrane, Mourad; Ismail, Dahlia; Garrigue, Jean-Sebastien; Figueiredo, Francisco C.; Baudouin, Christophe
Purpose: The SANSIKA study was conducted to assess the treatment effect of 0.1% cyclosporine A cationic emulsion (CsA CE) eye drops on signs and symptoms of patients with severe dry eye disease (DED). Methods: This was a multicenter, randomized, double-masked, 2-parallel-arm, 6-month phase III study with a 6-month open-label treatment safety follow-up. Patients with severe DED with corneal fluorescein staining (CFS) grade 4 on the modified Oxford scale were randomized to receive once-daily CsA CE (Ikervis®) or its vehicle. Results: A total of 246 patients were randomized. The proportion of patients achieving ≥2 grades improvement in CFS and a 30% improvement in symptoms (Ocular Surface Disease Index [OSDI]) by month 6 was 28.6% with CsA CE vs 23.1% with vehicle (p = 0.326) (primary endpoint). Assessment of corneal damage showed greater improvement with CsA CE over vehicle in mean adjusted CFS change from baseline to month 6 (-1.764 vs −1.418, p = 0.037). There was a reduction in ocular surface inflammation assessed by human leukocyte antigen DR expression in favor of CsA CE at month 6 (p = 0.021). The mean OSDI change from baseline was −13.6 with CsA CE and −14.1 with vehicle at month 6 (p = 0.858). The main adverse event was instillation site pain (29.2% vs 8.9% in the CsA CE and vehicle groups, respectively), and it was mostly mild. Conclusions: CsA CE was well-tolerated and effective in improving corneal damage and ocular surface inflammation and confirmed the positive benefit-risk ratio of this new formulation of CsA for the treatment of severe keratitis in DED.